2022
DOI: 10.1007/s11356-022-22256-w
|View full text |Cite
|
Sign up to set email alerts
|

The impact of economic uncertainty, economic growth and energy consumption on environmental degradation in MENA countries: Fresh insights from multiple thresholds NARDL approach

Abstract: This paper explores the influence of economic policy uncertainty on environmental quality in selected MENA countries depending on an augmented STIRPAT model over the period 1970–2020. ARDL model and its extensions like augmented ARDL, augmented NARDL, and MTNARDL models are applied to detect any possible effect from uncertainty index to carbon dioxide (CO 2 ) emissions. The empirical results reveal the validity of environmental Kuznet curve (EKC) curve in all the countries. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 103 publications
(143 reference statements)
1
9
1
Order By: Relevance
“…In Model 3, blue economic factors are added to the equation. The coefficient of positive shocks in the fishery is insignificant but negative shocks are significantly and positively related to economic growth at a 10% significance level, which is against the results of Ayad et al (2022); Y. Huang et al (2022); Jawaid et al (2019).…”
Section: Resultscontrasting
confidence: 60%
“…In Model 3, blue economic factors are added to the equation. The coefficient of positive shocks in the fishery is insignificant but negative shocks are significantly and positively related to economic growth at a 10% significance level, which is against the results of Ayad et al (2022); Y. Huang et al (2022); Jawaid et al (2019).…”
Section: Resultscontrasting
confidence: 60%
“…As a result, individuals and companies relied more on cheap traditional energy sources such as coal and oil, which are major contributors to greenhouse gas emissions. Furthermore, high EPU can negatively impact renewable energy investments in Egypt, leading to further reliance on fossil fuels (Ayad et al 2023 ).…”
Section: Empirical Findings and Discussionmentioning
confidence: 99%
“…Similarly, Ayad et al (2023) conducted an empirical study and found evidence supporting the EKC hypothesis in countries such as Algeria, Egypt, Iran, Morocco, and others. In South Asian countries, Murshed (2021) demonstrated that the EKC hypothesis exists in India, Bhutan, Bangladesh, and Sri Lanka.…”
Section: Introductionmentioning
confidence: 93%